การเปรียบประสิทธิภาพกลุ่มหลักทรัพย์ตามปัจจัยพื้นฐานกลุ่มหลักทรัพย์ ตามอุตสาหกรรม และกลุ่มหลักทรัพย์สุ่มเลือก โดยใช้แบบจำลองราคาสี่ปัจจัย - เกรียงไกร ก้อนคำ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
The objective of this independent study is to compare the performances of portfolio constructed using fundamental factors, industrial factors, and random selection. The performances of portfolio are measured by Jensen’s Alpha (α) which is the excess returns from the four-factor pricing model. By running the regression using daily data on each portfolio during January 2007 to December 2012, the alpha value is derived and is used to compare the performance across portfolios. Results of performance comparison show that only fundamental portfolio has the excess return significant different from zero, and has the coefficient of variation lower than that other portfolio with the coefficient of determination (adjusted R2) equal to 88.3%. From these results, it can be conclude that four-factor pricing model is appropriate to explore the returns and the performance of portfolio constructed using fundamental factor is the superior portfolio relative to other portfolios. The study shows that the investor should be focused on fundamental portfolio and use as guidelines investment in the stock exchange of Thailand. If consider to risk factors in the four-factor pricing model, it also show that market premium, size premium, and value premium related to the rate of return on three groups of portfolio but momentum premium cannot explain rate of return on the portfolio.